1996
DOI: 10.1016/0014-5793(96)00621-7
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane topology of Escherichia coli H+‐ATPase (ATP synthase) subunit a

Abstract: Escherichia coli H+-ATPase subunit a is a hydrophobic Fo subunit. To investigate the topology of the subunit in the membrane, we prepared site-specific polyclonal antibodies against amino-terminal (Ser-3 to Leu-16), middle loop (Lys-167 to Gin-181), and carboxyl-terminal (Thr-259 to His-271) peptide segments. Enzyme-linked immunosorbent assay revealed that these antibodies specifically reacted with subunit a of inside-out membrane vesicles, but not with that of right-side-out spheroplasts. Full reactivity appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Yamada et al (18) reported a preliminary topographical model for subunit a based upon the binding of three antipeptide-directed antisera to ISO membrane vesicles bound to microtiter plates. The location of the COOH terminus and a cytoplasmic loop agrees with the topographical model predicted here, but the NH 2 terminus was also concluded to be cytoplasmic, leading to a six-helix model.…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al (18) reported a preliminary topographical model for subunit a based upon the binding of three antipeptide-directed antisera to ISO membrane vesicles bound to microtiter plates. The location of the COOH terminus and a cytoplasmic loop agrees with the topographical model predicted here, but the NH 2 terminus was also concluded to be cytoplasmic, leading to a six-helix model.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies using the labeling of cysteine substitutions (18,19), epitope insertions (20), and peptide-directed antibodies (20,21), to identify surface accessible regions of the protein have come to significant agreement. However, the location of the N terminus remains controversial, leading to models of five-or six-transmembrane spans.…”
mentioning
confidence: 99%
“…Studies using the labeling of cysteine substitutions (18,19) concluded five-transmembrane spans, with a periplasmic N terminus. Studies using epitope insertion and peptide-directed antibodies (20,21) found cytoplasmic localization of the N terminus, leading to six-transmembrane spans. All of the studies required the preparation of oriented membrane vesicles for probing potentially accessible surface residues or regions.…”
mentioning
confidence: 99%
“…The b subunits attach the a subunit to an ␣ subunit of the ␣ 3 ␤ 3 headpiece via the ␦ subunit (18,19). The a subunit is an integral membrane protein consisting of five or six membranespanning ␣-helices (20)(21)(22)(23). According to NMR analyses of E. coli subunit c in chloroform͞methanol͞water, the two helices pack closely to one another, extending over 40 and 30 residues, respectively, with a short interruption after D61 of the Cterminal ␣-helix (24).…”
mentioning
confidence: 99%